Barium‐doped Sr2Fe1.5Mo0.5O6‐δ perovskite anode materials for protonic ceramic fuel cells for ethane conversion. Issue 5 (13th January 2022) - Fan, Yun; Xi, Xiuan; Li, Jun; Wang, Qi; Xiang, Kun; Medvedev, Dmitry; Luo, Jing‐Li; Fu, Xian‐Zhu
Abstract: Protonic ceramic ethane fuel cells fed by hydrocarbon fuels are demonstrated to be effective energy conversion devices. However, their practical application is impeded by a lack of anode materials combining excellent catalytic activity with good chemical stability and anti‐carbon deposition properties. In this work, in which Sr2 Fe1.5 Mo0.5 O6‐ δ (SFM) double perovskite oxide is used as the matrix framework, catalytic activity toward H2 and C2 H6 oxidation is systematically investigated using Ba‐doping. It is found that the concentration of the oxygen vacancy is gradually improved with increased Ba content to significantly enhance catalytic activity toward H2 and C2 H6 oxidation. From the series studied, Ba0.6 Sr1.4 Fe1.5 Mo0.5 O6‐ δ exhibits the highest catalytic activity, while the power densities of the electrolyte‐supported Ba0.6 SFM/BaCe0.7 Zr0.1 Y0.2 O3‐ δ (BCZY)/La0.58 Sr0.4 Co0.2 Fe0.8 O3‐ δ (LSCF)‐Sm0.2 Ce0.8 O2‐δ (SDC) single cell reach 205 and 138 mW cm –2 at 750°C in H2 and C2 H6, respectively. The ethane conversion rate of the experimental cell is shown to reach 38.4%, while simultaneously maintaining ethylene selectivity at 95%. Furthermore, the single cell exhibits no significant attenuation during stable operation for 20 h, as well as demonstrating excellent anti‐coking performance. The proposed results suggest that Ba0.6 Sr1.4 Fe1.5 Mo0.5 O6‐ δ represents a promising anode material for efficient hydrocarbon‐related electrochemical conversion to realize the coproduction of ethylene and power in protonic ceramic ethane fuel cells. Abstract : The large radius Ba‐ions are doped in the A site of the double perovskite ceramic structure, the active oxygen vacancy of the anode can be promoted by adjusting the Ba/Sr ratio to improve the electrocatalytic performance of the anode, effectively realize the coproduction of ethylene and power in protonic ceramic ethane fuel cells.